Sharing stories and the creative challenge of keeping them alive: interview with Steven High, founder of the Centre for Oral History and Digital Storytelling at Concordia University, in Montreal - Coelho Jucá dos Santos, Mayra (História Oral, 2022)
Interview with Steven High, a Canadian oral historian and acclaimed author of over a dozen books, founder of the Centre for Oral History and Digital Storytelling (COHDS) at Concordia University. Since its launch in 2006, COHDS became a reference at diverse levels, from the models of partnership beyond the academy gates, involving researchers, artists and community leaders, amongst other connections, to its use of digital technologies and the promotion of intersections between oral history and creative productions such as theatre, museum exhibitions, sound-walks and films. In this interview, Steven High gives us an in-depth look at his approach to oral history, the research-creation process and digital tools developed by COHDS over the last 15 years, and discusses how oral history can be transformed from a disciplinary methodology into an interdisciplinary creative practice.